Lithium ion battery silicon-based negative electrode material with small volume expansion and preparation method thereof
By covering silicon material on the surface of the carbon nanotube and covering carbon layers on the outer surface, and combining special processes to arrange the carbon nanotubes in an orderly manner, the problem of silicon volume effect in lithium-ion batteries is solved, and the cycle stability and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510154854.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-12
AI Technical Summary
The huge volume effect of pure silicon in lithium-ion batteries during charging and discharging limits its practical application.
Carbon nanotubes are used as substrates to coat silicon material on their surfaces, and carbon layer is coated on the outer surface through chemical deposition. Finally, the carbon nanotubes are arranged in an orderly manner through a special process to form a honeycomb-like structure.
It effectively suppresses the volume expansion of silicon material during charging and discharging, and improves the cycle stability and rate performance of lithium-ion batteries.
Smart Images

Figure CN119627054A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy battery electrode materials, and in particular to a lithium-ion battery silicon-based negative electrode material with small volume expansion and a preparation method thereof. Background Art
[0002] With the rapid development of energy storage facilities and electric vehicles, the market demand for lithium-ion batteries with high energy density, long cycle life and excellent rate performance has become increasingly urgent. Graphite, due to its relatively low theoretical lithium storage capacity, is unable to meet the development needs of high-energy-density lithium-ion batteries. Silicon has many significant advantages, such as high theoretical capacity, low discharge voltage, low cost and environmental friendliness. However, during the charging and discharging process, pure silicon will produce a huge volume effect, which greatly limits its practical application.
[0003] To solve this problem, researchers have changed the morphology of silicon to prepare silicon nanowires, nanotubes, hollow nanospheres, nanofilms, and silicon / carbon composite materials. The abundant voids in porous materials can effectively absorb the stress generated by the silicon embedding / de-embedding process, thereby alleviating the volume effect problem of the electrode.
[0004] For silicon / carbon composite materials, the commonly used methods are to embed silicon-based materials into the pores of carbon-based materials, or to use carbon-based materials to cover silicon-based materials to obtain core-shell structures. If the pores and other transport channels are arranged in sequence, it will be more conducive to improving battery performance. However, there are few studies in this area. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the present invention provides a silicon-based negative electrode material for a lithium-ion battery, using carbon nanotubes as a matrix to coat a silicon material on its surface, and finally chemically depositing a carbon material on the outer surface. The carbon nanotubes are arranged in an orderly manner through a special process, thereby improving the cycle stability and rate performance of the lithium-ion battery.
[0006] Specifically: A method for preparing a lithium-ion battery silicon-based negative electrode material with small volume expansion, the steps comprising: Step 1: Place the carbon nanotubes in a container, add a mixed acid of sulfuric acid and nitric acid, completely immerse the carbon nanotubes in the acid solution, stir to react for 1-2 hours, filter and remove the filtrate to obtain a substrate; Step 2, washing the substrate obtained in step 1 to neutrality, and vacuum drying to obtain pretreated carbon nanotubes; Step 3, dispersing the carbon nanotubes pretreated in step 2 in an ethanol solution, ultrasonically dispersing, and setting aside; Step 4: mix ethyl orthosilicate with water, hydrochloric acid and dodecyltrimethylammonium chloride in a mass ratio of 200:70:4-18:3-30 to form a mixed solution; Step 5, slowly adding the mixed solution of step 4 to the carbon nanotube dispersion of step 3 under stirring conditions, heating for reaction, separating the product after the reaction is completed, and vacuum drying to obtain silica gel-modified carbon nanotubes; Step 6: Mix the carbon nanotubes modified with silica gel in step 5 with magnesium powder, grind them and place them in a reaction furnace, fill the furnace with inert gas, heat it to 630-680°C, keep it warm for 4-6 hours, take out the product and immerse it in hydrochloric acid solution for 10-14 hours, filter and wash it to obtain silicon-modified carbon nanotubes; Step 7: Add the silicon-modified carbon nanotubes prepared in step 6 to an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid, stir for 2-3 hours, keep warm at 100-120°C for 8-10 hours, heat to 160-180°C for 8-10 hours, then move to a reactor, fill with inert gas, and keep warm at 900°C for 8-10 hours to finally obtain a silicon-based negative electrode material for lithium-ion batteries.
[0007] Furthermore, the carbon nanotubes are multi-walled carbon nanotubes.
[0008] Furthermore, in step 1, the volume ratio of sulfuric acid to nitric acid is 3:1.
[0009] Furthermore, in step five, the reaction temperature is controlled at 60-80° C., and the reaction time is 12-20 h.
[0010] Furthermore, in step five, centrifugal separation is performed, and the separated product is washed with ethanol and then vacuum dried.
[0011] Furthermore, in step five, the mass ratio of the mixed solution to the carbon nanotubes is 40-50:1.
[0012] Furthermore, in step six, the mass ratio of the silica gel-modified carbon nanotubes to the magnesium powder is 2-5:1.
[0013] Furthermore, the heating rate of step six is 5°C / min.
[0014] Furthermore, in step 7, the mass fraction of sodium lignin sulfonate in the aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is 16%-22%, and the mass fraction of concentrated sulfuric acid is 1.5%-2.5%; 5-7 mL of the aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is required for every 1 g of silicon-modified carbon nanotubes.
[0015] On the other hand, the present invention provides a lithium-ion battery silicon-based negative electrode material with small volume expansion, which is prepared by the above-mentioned preparation method.
[0016] Compared with the prior art, the present invention has the following beneficial features: 1. The present invention adopts carbon nanotubes as a matrix, and the hollow tube cavity and tube wall of the carbon nanotubes provide abundant storage space and transportation channels for lithium ions; first, silicone gel is generated on the surface of the carbon nanotubes, and then the treated carbon nanotubes are mixed with magnesium powder and heated to melt the magnesium powder, and the originally disordered carbon nanotubes are wetted and soaked in the magnesium melt. Due to the directional effect of the liquid, the carbon nanotubes are orderly arranged in parallel, and the hollow tube cavity of the carbon nanotubes is arranged to form a honeycomb-like structure, and finally a carbon layer is coated on the surface by chemical deposition, thereby inhibiting the volume expansion of the silicon material during discharge; the prepared negative electrode material is convenient for lithium ion transportation due to the orderly arrangement of the hollow tube cavity of the carbon nanotubes, thereby improving the cycle stability and rate performance of the battery.
[0017] 2. In the preparation method of the present invention, the carbon nanotubes are first treated with acid so that the surface of the carbon nanotubes has a negative charge. The quaternary ammonium head group of dodecyltrimethylammonium chloride is positively charged, so it will be adsorbed on the surface of the carbon nanotubes through electrostatic attraction. Electrostatic attraction is a strong interaction force, which ensures that dodecyltrimethylammonium chloride preferentially gathers around the carbon nanotubes. After being adsorbed on the surface of the carbon nanotubes, dodecyltrimethylammonium chloride will self-assemble. Due to the presence of its hydrophobic chains, they tend to gather together to form a certain ordered structure, thereby constructing a specific microenvironment on the surface of the carbon nanotubes. This self-assembled structure provides a steric hindrance, so that the hydrolysis and polycondensation reaction of ethyl orthosilicate is more inclined to proceed in this area, because the silicon source molecules are more likely to enter the microenvironment formed by the dodecyltrimethylammonium chloride molecules, where a hydrolysis reaction occurs, and the formed silicic acid product will further polycondense to form a silica gel.
[0018] 3. In the preparation method of the present invention, magnesium powder is melted, which not only makes the originally disordered carbon nanotubes orderly, but also the magnesium metal liquid can reduce the silica gel, so that more silica gel is converted into elemental silicon. More elemental silicon is beneficial for application in scenarios with higher requirements for energy density and fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0020] Figure 1 This is a SEM image of the silicon-based negative electrode material for a lithium-ion battery in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In order to facilitate those skilled in the art to implement the present invention, some of the reagents used in the embodiments and comparative examples are now described: Carbon nanotubes: multi-walled carbon nanotubes, Shandong Carbon Peak New Materials Technology; Sulfuric acid: Hengfeng Chemical, homemade, mass fraction 80%; Nitric acid: Hengfeng Chemical, homemade, mass fraction 65%; Ethanol: anhydrous ethanol, Shandong Mengkangda Chemical; Tetraethyl orthosilicate: Jinan Shuangying Chemical; Hydrochloric acid: Hengfeng Chemical, homemade, mass fraction 3%; Dodecyltrimethylammonium chloride: Jinan Rongzheng Chemical; Magnesium powder: Changzhou Meiyao Chemical; Inert gas: argon, Zhongshan Aojia; Sodium lignin sulfonate: Shandong Jinli Chemical; Concentrated sulfuric acid: Hengfeng Chemical, mass fraction 98%.
[0023] In order to verify the beneficial effects of the present invention, the following embodiments and comparative examples are designed and tested to verify them.
[0024] Example 1
[0025] A lithium-ion battery silicon-based negative electrode material with small volume expansion, the preparation steps of which include: Step 1: Place the carbon nanotubes in a container, add a mixed acid of sulfuric acid and nitric acid (the volume ratio of sulfuric acid to nitric acid is 3:1), completely immerse the carbon nanotubes in the acid solution, stir to react for 1 hour, filter and remove the filtrate to obtain the substrate; Step 2: washing the substrate obtained in step 1 to neutrality, and vacuum drying at 60° C. for 24 h to obtain pretreated carbon nanotubes; Step 3, dispersing the carbon nanotubes pretreated in step 2 in an ethanol solution, ultrasonically dispersing for 30 minutes, and setting aside; Step 4: mix ethyl orthosilicate with water, hydrochloric acid and dodecyltrimethylammonium chloride in a mass ratio of 200:70:4:3 to form a mixed solution; Step 5: slowly add the mixed solution of step 4 to the carbon nanotube dispersion of step 3 under stirring conditions, heat to 60° C., react for 20 h, centrifuge to separate the product after the reaction is completed, wash with ethanol, and then vacuum dry at 60° C. for 24 h to obtain silica gel-modified carbon nanotubes; Step 6: Mix the carbon nanotubes modified with silica gel in step 5 with magnesium powder in a mass ratio of 2:1, place in a reaction furnace after ball milling, fill the furnace with inert gas, heat to 630°C at a rate of 5°C / min, keep warm for 6 hours, take out the product and immerse it in hydrochloric acid solution for 14 hours, filter and wash, and obtain silicon-modified carbon nanotubes; Step 7: Add the silicon-modified carbon nanotubes prepared in step 6 to an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid. 5 mL of an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is required for every 1 g of silicon-modified carbon nanotubes. The mass fraction of sodium lignin sulfonate is 16%, and the mass fraction of concentrated sulfuric acid is 1.5%. Stir for 3 h, keep warm at 100 ° C for 10 h, heat to 160 ° C for 10 h, then move to a reactor, fill with inert gas, and keep warm at 900 ° C for 10 h to finally obtain a silicon-based negative electrode material for lithium-ion batteries.
[0026] like Figure 1 As shown, the prepared lithium-ion battery silicon-based negative electrode material is arranged in an orderly manner.
[0027] Example 2
[0028] A lithium-ion battery silicon-based negative electrode material with small volume expansion, the preparation steps of which include: Step 1: Place the carbon nanotubes in a container, add a mixed acid of sulfuric acid and nitric acid (the volume ratio of sulfuric acid to nitric acid is 3:1), completely immerse the carbon nanotubes in the acid solution, stir to react for 2 hours, filter and remove the filtrate to obtain a substrate; Step 2: washing the substrate obtained in step 1 to neutrality, and vacuum drying at 80° C. for 12 h to obtain pretreated carbon nanotubes; Step 3, dispersing the carbon nanotubes pretreated in step 2 in an ethanol solution, ultrasonically dispersing for 30 minutes, and setting aside; Step 4: mix ethyl orthosilicate with water, hydrochloric acid and dodecyltrimethylammonium chloride in a mass ratio of 200:70:18:30 to form a mixed solution; Step 5, slowly adding the mixed solution of step 4 to the carbon nanotube dispersion of step 3 under stirring conditions, heating to 80°C, reacting for 12 hours, centrifuging and separating the product after the reaction is completed, washing with ethanol, and then vacuum drying at 80°C for 12 hours to obtain silica gel-modified carbon nanotubes; Step 6: Mix the carbon nanotubes modified with silica gel in step 5 with magnesium powder in a mass ratio of 5:1, place in a reaction furnace after ball milling, fill the furnace with inert gas, heat to 680°C at a rate of 5°C / min, keep warm for 4 hours, take out the product and immerse it in hydrochloric acid solution for 10 hours, filter and wash, and obtain silicon-modified carbon nanotubes; Step 7: Add the silicon-modified carbon nanotubes prepared in step 6 to an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid. 5-7 mL of an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is required for every 1 g of silicon-modified carbon nanotubes. The mass fraction of sodium lignin sulfonate is 22% and the mass fraction of concentrated sulfuric acid is 2.5%. Stir for 2 h and keep warm at 120 ° C for 8 h. Heat to 180 ° C and keep warm for 8 h. Then move to a reactor, fill with inert gas, and keep warm at 900 ° C for 8 h to finally obtain a silicon-based negative electrode material for lithium-ion batteries.
[0029] Example 3
[0030] A lithium-ion battery silicon-based negative electrode material with small volume expansion, the preparation steps of which include: Step 1: Place the carbon nanotubes in a container, add a mixed acid of sulfuric acid and nitric acid (the volume ratio of sulfuric acid to nitric acid is 3:1), completely immerse the carbon nanotubes in the acid solution, stir to react for 1 hour, filter and remove the filtrate to obtain the substrate; Step 2: washing the substrate obtained in step 1 to neutrality, and vacuum drying at 70° C. for 20 h to obtain pretreated carbon nanotubes; Step 3, dispersing the carbon nanotubes pretreated in step 2 in an ethanol solution, ultrasonically dispersing for 50 minutes, and setting aside; Step 4: mix ethyl orthosilicate with water, hydrochloric acid and dodecyltrimethylammonium chloride in a mass ratio of 200:70:10:20 to form a mixed solution; Step 5: slowly add the mixed solution of step 4 to the carbon nanotube dispersion of step 3 under stirring conditions, heat to 70°C, and react for 15 hours. After the reaction is completed, centrifuge to separate the product, wash with ethanol, and then vacuum dry at 70°C for 18 hours to obtain silica gel-modified carbon nanotubes; Step 6: Mix the carbon nanotubes modified with silica gel in step 5 with magnesium powder in a mass ratio of 3:1, place in a reaction furnace after ball milling, fill the furnace with inert gas, heat to 650°C at a rate of 5°C / min, keep warm for 5h, take out the product and immerse it in hydrochloric acid solution for 12h, filter and wash, and obtain silicon-modified carbon nanotubes; Step 7: Add the silicon-modified carbon nanotubes prepared in step 6 to an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid. 5-7 mL of an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is required for every 1 g of silicon-modified carbon nanotubes. The mass fraction of sodium lignin sulfonate is 20% and the mass fraction of concentrated sulfuric acid is 2%. Stir for 2-3 hours and keep warm at 110°C for 9 hours. Heat to 170°C and keep warm for 9 hours. Then move to a reactor, fill with inert gas, and keep warm at 900°C for 9 hours to finally obtain a silicon-based negative electrode material for lithium-ion batteries.
[0031] Comparative Example 1 A lithium-ion battery silicon-based negative electrode material, the preparation steps of which include: Step 1: Place the carbon nanotubes in a container, add a mixed acid of sulfuric acid and nitric acid (the volume ratio of sulfuric acid to nitric acid is 3:1), completely immerse the carbon nanotubes in the acid solution, stir to react for 1-2 hours, filter and remove the filtrate to obtain the substrate; Step 2: washing the substrate obtained in step 1 to neutrality, and vacuum drying at 60-80° C. for 12-24 hours to obtain pretreated carbon nanotubes; Step 3, dispersing the carbon nanotubes pretreated in step 2 in an ethanol solution, ultrasonically dispersing for 30-60 minutes, and setting aside; Step 4: mix ethyl orthosilicate with water, hydrochloric acid and dodecyltrimethylammonium chloride in a mass ratio of 200:70:4-18:3-30 to form a mixed solution; Step 5, slowly adding the mixed solution of step 4 to the carbon nanotube dispersion of step 3 under stirring conditions, heating to 60-80°C, reacting for 12-20 hours, centrifuging and separating the product after the reaction is completed, washing with ethanol, and then vacuum drying at 60-80°C for 12-24 hours to obtain silica gel-modified carbon nanotubes; Step 6: Add the carbon nanotubes modified with silicon gel in step 5 to an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid. 5-7 mL of an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is required for every 1 g of silicon-modified carbon nanotubes. The mass fraction of sodium lignin sulfonate is 16%-22%, and the mass fraction of concentrated sulfuric acid is 1.5%-2.5%. Stir for 2-3 hours, keep warm at 100-120°C for 8-10 hours, heat to 160-180°C for 8-10 hours, then move to a reactor, fill with inert gas, and keep warm at 900°C for 8-10 hours to finally obtain a silicon-based negative electrode material for lithium-ion batteries.
[0032] The lithium-ion battery silicon-based negative electrode materials obtained in the above Examples 1-3 and Comparative Example 1 were applied to batteries to conduct battery performance tests.
[0033] Battery assembly: The negative electrode material, conductive agent (SP), CMC and SBR are mixed in a mass ratio of 95:1.5:1.5:2, and coated on copper foil to obtain a negative electrode sheet; the positive electrode active material lithium cobalt oxide, conductive agent (SP) and PVDF are mixed evenly in a mass ratio of 96.5:2:1.5 and coated on aluminum foil to obtain a positive electrode sheet; the electrolyte is 1 mol / L LiPF6+EC+EMC; the diaphragm is a polyethylene / propylene composite microporous membrane; the above materials are assembled into CR2025 button batteries.
[0034] Test method: The battery was charged and discharged using a LAND 2001A battery tester. The charge and discharge voltage range was set to 0.01-2.0V (vsLi / Li+). The specific capacity (mAh / g) was tested when the current density increased from 0.1A / g to 0.5A / g, 1.0A / g, 1.5A / g and 2.0A / g, and then the current density was restored to 0.1A·g. -1 Specific capacity (mAh / g) at 370 °C.
[0035] The test results are shown in the following table:
[0036] It can be seen from the above test results that the negative electrode materials of Examples 1-3 have better capacity stability in the rate test than that of Comparative Example 1. The difference between Comparative Example 1 and Examples 1-3 is that the carbon nanotubes are orderly arranged in parallel by using magnesium metal liquid.
[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a silicon-based negative electrode material for a lithium-ion battery with small volume expansion, characterized in that: The steps include: Step 1: Place the carbon nanotubes in a container, add a mixed acid of sulfuric acid and nitric acid, completely immerse the carbon nanotubes in the acid solution, stir to react for 1-2 hours, filter and remove the filtrate to obtain a substrate; Step 2, washing the substrate obtained in step 1 to neutrality, and vacuum drying to obtain pretreated carbon nanotubes; Step 3, dispersing the carbon nanotubes pretreated in step 2 in an ethanol solution, ultrasonically dispersing, and setting aside; Step 4: mix ethyl orthosilicate with water, hydrochloric acid and dodecyltrimethylammonium chloride in a mass ratio of 200:70:4-18:3-30 to form a mixed solution; Step 5, slowly adding the mixed solution of step 4 to the carbon nanotube dispersion of step 3 under stirring conditions, heating for reaction, separating the product after the reaction is completed, and vacuum drying to obtain silica gel-modified carbon nanotubes; Step 6: Mix the carbon nanotubes modified with silica gel in step 5 with magnesium powder, grind them and place them in a reaction furnace, fill the furnace with inert gas, heat it to 630-680°C, keep it warm for 4-6 hours, take out the product and immerse it in hydrochloric acid solution for 10-14 hours, filter and wash it to obtain silicon-modified carbon nanotubes; Step 7: Add the silicon-modified carbon nanotubes prepared in step 6 to an aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid, stir for 2-3 hours, keep warm at 100-120°C for 8-10 hours, heat to 160-180°C for 8-10 hours, then move to a reactor, fill with inert gas, and keep warm at 900°C for 8-10 hours to finally obtain a silicon-based negative electrode material for lithium-ion batteries.
2. The preparation method according to claim 1, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes.
3. The preparation method according to claim 1, characterized in that: The volume ratio of sulfuric acid to nitric acid in step 1 is 3:
1.
4. The preparation method according to claim 1, characterized in that: In step 5, the reaction temperature is controlled at 60-80°C and the reaction time is 12-20h.
5. The preparation method according to claim 1, characterized in that: Step five is to separate by centrifugation, and the separated product is washed with ethanol and then vacuum dried.
6. The preparation method according to claim 1, characterized in that: In step 5, the mass ratio of the mixed solution to the carbon nanotubes is 40-50:
1.
7. The preparation method according to claim 1, characterized in that: In step six, the mass ratio of the silica gel-modified carbon nanotubes to the magnesium powder is 2-5:
1.
8. The preparation method according to claim 1, characterized in that: The heating rate in step six is 5°C / min.
9. The preparation method according to claim 1, characterized in that: In step 7, the mass fraction of sodium lignin sulfonate in the aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is 16%-22%, and the mass fraction of concentrated sulfuric acid is 1.5%-2.5%; 5-7 mL of the aqueous solution containing sodium lignin sulfonate and concentrated sulfuric acid is required for every 1 g of silicon-modified carbon nanotubes.
10. A lithium-ion battery silicon-based negative electrode material with small volume expansion, characterized in that: The method is as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and application of multiwalled carbon nanotube / silicon and silicon oxide / carbon composite nanomaterial
CN108493432A
Silicon / carbon nanotube composite material, preparation method thereof, lithium battery negative electrode and lithium battery
CN111082014A
Preparation method and application of carbon nanotube-loaded carbon-coated silica material
CN112635734A
Preparing method of size-controlled silicon carbide powder
KR101627371B1
Fibrous carbon aerogels coated with nano-thin silicon as lithium battery anodes
US20220209234A1